A Study on Performance of Cricket Players using Factor Analysis Approach (International Journal of Advanced Research in Computer Science, 2017)
In this paper, an attempt has been made to study the performance of Cricket Players using Factor Analysis technique. For this , the dataset of 85 batsmen, 85 bowlers; and 95 batsmen, 95 bowlers have been considered from IPL9, 2016 (20 overs) and ICC World Cup, 2015 (50 overs) respectively, and the findings of this study reveals that batting capability dominates over bowling capability which is in conformity with an earlier study on same kind of game. Keywords: Factor Analysis, World Cup, IPL, Cricket.